2009
DOI: 10.1177/0042098008098635
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Change and the Housing Market: Evidence from a Comparison of Scotland and England

Abstract: This paper examines the impact of demographic change on the housing market. More specifically, a difference-in-differences methodology is used to explore the effect of population decline and population ageing on house prices in Scotland and England/Wales. The analysis suggests that population decline and population ageing put downward pressure on prices. Therefore, the long-run trend of rising real house prices can not be assumed to continue into the future, particularly in Scotland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 29 publications
0
36
0
1
Order By: Relevance
“…Instead, these are estimated using variation in age structure and house prices across regional units. For a similar argument, see (Levin et al 2009). …”
Section: Introductionmentioning
confidence: 75%
“…Instead, these are estimated using variation in age structure and house prices across regional units. For a similar argument, see (Levin et al 2009). …”
Section: Introductionmentioning
confidence: 75%
“…Ermisch [4] started to modify the model, considering the influence of other variables such as income and the supply of house, then he controlled the variables of income and the supply of house, etc., finding that the population age structure carries significant impact on housing demand, and argued that with the aging population increasing, housing demand would decrease and housing prices would fall. Levin [5] revised Mankiw-Weil model from another angle, using time series data of England and Scotland with the control variables of wealth and income, and carried the conclusion that shrinking population and aging population would have downward pressure on housing demand and prices. Domestic research literature on the impact of population age structure changes on real estate prices carried mainly after the 1998, this is mainly because the welfare housing distribution system abolished in 1998.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While in terms of abroad, the first category is the cross section data, such as Mankiw and Weil [1]. The second type is based on time series data, such as Lindh and Mahnberg, Levin [5]. However, panel data used to study is very little, and in terms of domestic part, conclusions about the impact of population age structure change on the real estate prices are not unified: negative correlation, positive correlation, and even no effect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research from the United States (Haurin, Hendershott, & Kim, 1993) and the United Kingdom (Ermisch, 1999;Levin, Montagnoli, & Wright, 2009) has shown that young people are less likely to leave the parental home or form independent households during times of high housing prices or when they live in metropolitan areas where housing is more expensive. There can Downloaded by [University of California, Los Angeles (UCLA)] at 10:12 16 May 2013 6 P. Monkkonen be long-run ramifications, however.…”
Section: Economic Development and Housing Deficitsmentioning
confidence: 99%